The rising cases of suicide among Nigerians: what are the risk factors, prevention, and remedies? - Nnaemeka Chukwudum Abamara; Onyinye Ezinne Ozongwu (Consortium Psychiatricum, 2024)
The escalating suicide rate in Nigeria, exacerbated by economic, political, health, and social crises, represents a pressing concern. The aftermath of the global COVID-19 pandemic and subsequent lockdowns has exacerbated this issue, particularly in African nations with bare-bones governmental support systems. This paper examines the underlying causes of the alarming number of suicides in Nigeria, utilizing interviews to explore the risk factors, preventative measures adopted, and crisis interventions. Our findings reveal that spousal conflicts, job loss, and bereavement are significant triggers of suicidal ideation. Recommendations include fostering supportive environments, crisis interventions, and psychological rehabilitation services. Urgent attention is warranted to address this growing trend and mitigate its socioeconomic repercussions in Nigeria.